Coronary microvascular dysfunction in autoimmune rheumatic diseases: beyond coronary flow velocity reserve - Cecere, Annagrazia; Perazzolo Marra, Martina; Zanatta, Elisabetta; Civieri, Giovanni; Iliceto, Sabino; Tona, Francesco (Frontiers in Cardiovascular Medicine, 2024)
Autoimmune rheumatic diseases (ARDs) are a heterogeneous group of disorders characterized by an inappropriate immune reactivity against different body tissues. Patients affected by ARDs present an increased cardiovascular morbidity and mortality, that significantly impacts on the long-term prognosis. Endothelial dysfunction, inflammation, oxidative stress and autoimmunity are strictly involved in atherosclerosis progression and coronary microvascular dysfunction (CMD), both responsible for the increased cardiovascular risk. CMD represents the inability of the coronary microvasculature to respond with vasodilation to the increased cardiac metabolic requests and it could be assessed by non-invasive and invasive imaging tests. Coronary flow velocity reserve assessed by echocardiography demonstrated to correctly identify ARDs patients with CMD. However, stress cardiac magnetic resonance (CMR) accurately assesses myocardial ischemia, perfusion and viability in ARDs patients. Myocardial perfusion reserve index (MPRI) is a robust semi-quantitative imaging marker, representing the vasodilatory capacity of the coronary microcirculation in response to a vasodilator stress. In absence of significant coronary stenosis, ARDs patients revealed a reduced MPRI in comparison with general population, regardless the presence of myocardial fibrosis.Identification of CMD in asymptomatic patients could be crucial to precociously start targeted medical therapy, avoiding major adverse cardiac events in this clinical setting. This review aims to summarize the current evidence regarding CMD in ARDs patients, focusing on the role of stress CMR and the promising myocardial perfusion analysis.